1988
DOI: 10.1002/pen.760282405
|View full text |Cite
|
Sign up to set email alerts
|

Memory effects in polymers. II. Processing history vs. crystallization rate of nylon 6—observation of phenomenon and product behavior

Abstract: The observation of a novel phenomenon is reported whereby the processing history of a nylon 6 leads to a memory effect which in turn affects its crystallization rate from the molten state. Differential scanning calorimetry (DSC) and optical microscopy are the primary techniques used to demonstrate that the melt‐crystallization behavior of nylon 6 can be controlled by processing variables. Characterization data is presented to show that obvious parameters such as molecular weight, impurities, monomer and oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 5 publications
4
36
0
Order By: Relevance
“…13,14,19 It is interesting that PA6 component in the noncompatibilized PP/PA6 blend exhibits a higher crystallization temperature (above 18.6 C or so, compared to the virgin PA6). This results is quite similar to the behavior on the PA6 homopolymer found by Khanna et al 20,21 and has been explained by a more ordered molecular arrangement that persists in the molten state due to the stabilizing effect of hydrogen bonding after melt extrusion of PA6. The virgin PA6 is thought to be disordered and to stay disordered in the molten state, again due to hydrogen bonding.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 79%
“…13,14,19 It is interesting that PA6 component in the noncompatibilized PP/PA6 blend exhibits a higher crystallization temperature (above 18.6 C or so, compared to the virgin PA6). This results is quite similar to the behavior on the PA6 homopolymer found by Khanna et al 20,21 and has been explained by a more ordered molecular arrangement that persists in the molten state due to the stabilizing effect of hydrogen bonding after melt extrusion of PA6. The virgin PA6 is thought to be disordered and to stay disordered in the molten state, again due to hydrogen bonding.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 79%
“…Khanna et al [21] also showed that extruded PA6 leads to faster crystallization than virgin PA6 under both isothermal and nonisothermal conditions. Fornes et al [28] proposed three possible reasons to explain such different crystalline behavior between the as-received virgin pellets and extruded PA6 materials: (1) Faster crystallization may arise from increased nucleation due to the presence of impurities incorporated in the matrix during processing.…”
Section: Crystalline Behaviormentioning
confidence: 94%
“…Consequently, the significant increase in crystallization rate from the virgin to the first processed PA6 should be due to memory effects induced by injection molding. More detail information about this phenomenon has been reported elsewhere [21][22][23][24][25][26][27][28]. For the samples with more than one processing step, the raise of crystallization rate is attributed to the decrease in molecular weight.…”
Section: Crystalline Behaviormentioning
confidence: 95%
“…The PA-6 crystallization temperature increases with w15 8C after extrusion. This is known as the memory effect and has been attributed to the break-up of a H-bond stabilized disordered structure in virgin PA-6 [24,25]. Hence, this decrease in overall crystallization rate only becomes apparent when extruded PA-6/MMT nanocomposites are compared to extruded pure PA-6.…”
Section: Introductionmentioning
confidence: 91%